Association between food intake and oral health in elderly: SEPAHAN systematic review no. 8 - Shantia Kazemi; Ghazal Savabi; Saber Khazaei; Omid Savabi; Ahmad Esmaillzadeh; Ammar Hassanzadeh Keshteli; Peyman Adibi (Wolters Kluwer Medknow Publications, 2011)
Dental status may influence food intake. The aim of this review was to summarize the earlier investigations on the association between food intake and dental status. We searched the electronic databases of PubMed and the Cochrane library for articles published until 30 February, 2012. To reach the related published articles, Medical Subject Heading (MeSH) terms of 'oral health,' 'masticatory performance,' 'dental status,' and 'eating' or 'food intake' were used. We included all research articles in the English language that (1) had used the random sampling method, and (2) had investigated the association between dental status and nutrient intake in elderly, non-denture wearer individuals, with no systemic illness. The findings of the seven original research articles had a great variation. Four of them supported a strong association between dietary intake and dental status and three of them found that there was no association between these variables. Most investigations found a significant relationship between the oral health status and nutrient intake; however, longitudinal studies were required for a better understanding of the diet-oral health relations.